Mucosal Snare Resection (MSR) in Non-Submucosal Injection Endoscopic Submucosal Excavation (NSI-ESE) for submucosal tumor may not be the preferable choice: A retrospective study - Jiatao Tu; Lixing Yu; Kaihan Wu; Meng Gu; Chencong Zhou; Xuan Huang (PLoS ONE, 2026)
Background and aims Non-submucosal injection endoscopic submucosal excavation (NSI-ESE) and mucosal snare resection-assisted endoscopic submucosal excavation (MSR-ESE) are novel techniques for the treatment of gastric submucosal tumors (SMTs). This study aims to evaluate the feasibility, safety, and efficacy differences between these two methods in the management of gastric SMTs. Methods A retrospective analysis was conducted on 95 eligible patients who underwent endoscopic treatment for gastric SMTs between 01/01/2022 and 31/12/2024, including 41 patients treated with MSR-ESE and 54 with NSI-ESE. Differences in operative time, safety, and cost-effectiveness between the two groups were compared, and multivariate linear regression analysis was performed to investigate the independent impact of the surgical approach on operative time. Results There were no significant differences between the two groups in baseline characteristics, en bloc resection rate, or incidence of adverse events such as intraoperative perforation and delayed bleeding. However, the MSR-ESE group had significantly longer tumor exposure time (6.37 ± 2.98 min vs. 4.61 ± 2.94 min, p = 0.001), tumor excavation time (29.59 ± 9.09 min vs. 24.09 ± 9.87 min, p = 0.007), and total procedure time (35.95 ± 10.23 min vs. 30.63 ± 11.61 min, p = 0.022) compared with the NSI-ESE group. Multivariate regression analysis confirmed that MSR-ESE was an independent factor associated with prolonged tumor exposure time (β = 1.60, p = 0.005) and total procedure time (β = 5.43, p = 0.012). In addition, the surgery-related cost was significantly higher in the MSR-ESE group than in the NSI-ESE group (US$874.94 ± 106.40 vs. US$731.90 ± 108.98, p < 0.038). Conclusion In the treatment of gastric SMTs, MSR-ESE did not demonstrate any advantages in efficiency or safety compared with NSI-ESE; instead, it resulted in a significantly longer procedure time, more discomfort and increased economic burden. Therefore, the routine use of snare-assisted mucosal resection during ESE is not recommended in clinical practice.